Penerapan Sistem Monitoring Lahan dan Analisa Neraca Air Klimatik Pertanian di Lahan Gambut - Bayu Dwi Apri Nugroho; Sri Nuryani Hidayah Utami; Benito Heru Purwanto (agriTECH, 2019)
Farming in peatland can produce a commodity well if it follows the right planting calendar. Microclimate conditions in the peatland cannot yet be measured in real-time within a shorter time interval. Pelalawan, a region where most of its farmers use peatland for oil palm cultivation, need guidance on applying the best method of oil palm cultivation, which is  possible to improve. This study aims to apply a telemetric based (field monitoring system) real-time climatic data application to monitor the agricultural field (peatland). Climate data and weather – soil sensors were set up in Pelalawan village from August 18 to November 16, 2018. Besides, the advancement of planting calendar determination method is also done for peatland farming with a climatic water balance analysis. The change in peatland farming has been successfully observed and measured. The changes in the climatic environment can be observed continuously within a time interval of 30 minutes. Sun radiation data show a significant fluctuation shift from day to day. It also occurs for rainfall, temperature and humidity data. Climatic data fluctuation can be monitored directly and continuously with a Field Monitoring System (FMS) application. Water balance for paddy and corn is obtained based on Plant Water Need and Effective Rain. The recommended schedule according to water balance analysis (surplus and deficit) is paddy 1 – corn – paddy 2.